Relationship Between Flowering Behaviour, Yield Characters and Hard Seededness in Mungbean Lines during Two Sowing Seasons - GAGANPREET KAUR; U. PARMAR; T.S. BAINS (Seed Research, 2026)
Two hard seeded (ML-613 and ML-131) and two non-hard seeded (NM-54 and Pusa-9972) mungbean lines were selected to study the relationship between flowering behaviour, yield characters and hard seededness during summer and kharif seasons. Non-hard seeded lines flowered and matured earlier than the hard seeded lines during both the seasons. Number of pods plant¹, number of seeds pod¹ and seed yield were maximum in hard seeded lines. On the other hand, pod length and 100 seed weight were significantly higher in non-hard seeded lines. Higher seed yield during the kharif season, was accompanied by increased hard seededness as compared to that in the summer season leading to more deterioration in seed quality.